Gambaran Tingkat Pengetahuan Ibu Tentang Stunting Pada Balita Di Puskesmas Kota Manna Kabupaten Bengkulu Selatan - Faradeisti, Reska; Paskana, Kristina; Gusnidarsih, Vevi (Gayaku Publisher, 2023)
Globally, stunting remains one of the main nutritional problems in infants and children under five years old. Stunting is a condition in children marked by length or height for age and sex less than -2 SD based on the World Health Organization (WHO) growth curve, due to chronic malnutrition associated with low socioeconomic conditions, poor nutritional intake and maternal health, a history of recurrent illness, and/or inappropriate infant and young child feeding practices. The purpose of this study was to determine the level of knowledge of mothers about stunting in toddlers at the Puskesmas Kota Manna, South Bengkulu Regency. The method used in this research is quantitative research with descriptive research method. The population of this study were all mothers who had toddlers in the working area of the Puskesmas Kota Manna, South Bengkulu Regency in June 2023 with 20 samples selected using the random sampling method. The results of this study obtained the age of the majority of respondents aged in the range of 20-35 years as many as 18 people (90.0%), the minority aged> 35 years as many as 2 people (10.0%). The majority of respondents' education is junior high school as many as 8 people (40.0%), the minority of SARJANA is 5 people (25.0%). The majority of respondents' occupations were housewives as many as 14 people (70.0%) and a minority of civil servants as many as 2 people (10.0%). the majority of respondents' knowledge was lacking, namely 9 people (45.0%) and a minority of sufficient knowledge as many as 7 people (35.0%). Based on the results of the study, the majority of mothers' knowledge about stunting in toddlers at the Puskesmas Kota Manna, South Bengkulu Regency in 2023 was less as many as 9 people (45.0%).